What does 0.5(-12p - 4) equal to?
1 answer:
Answer:
Use the distributive property to solve this equation: a(-b - c) = -ab - ac
Step-by-step explanation:
1. 0.5(-12p - 4) =
-6p - 2 is the answer.
Hope this helped!!!!
~Shane
You might be interested in
They could be 28 + 29 + 30
(-1,8) is the correct answer I’m pretty sure
Answer:
Not equivalent
Step-by-step explanation:
5:3
15:12 simplified = 5:4
Answer:
c.
Step-by-step explanation:
A1 = 2 (first term)
r = -1 (common ratio or second divided by first)